(untitled) (KONFERENSIYA, 2025)
The rapid digitalization of education has significantly transformed foreign language teaching and learning practices. Within this context, the development of communicative competence remains a central objective of language education, requiring reconsideration of traditional methodological approaches. This article proposes a methodological framework for developing communicative competence in digital learning environments. Drawing on communicative language teaching, competence-based education, and digital pedagogy, the study analyzes the structural components of communicative competence and identifies effective methodological tools for its development in online and blended learning contexts. The findings emphasize the role of interactivity, multimodality, learner autonomy, and formative assessment in enhancing communicative outcomes in digital environments.